2020
DOI: 10.1002/imhj.21882
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Newborn Behavioral Observations (NBO) system in early intervention: A multisite randomized controlled trial

Abstract: The purpose of this pilot study was to evaluate the effect of an infant mental health intervention, the Newborn Behavioral Observations system (NBO), versus usual care (UC) on infant neurodevelopment and maternal depressive symptoms in early intervention (EI). This multisite randomized trial enrolled newborns into the NBO (n = 16) or UC group (n = 22) and followed them for 6 months. Outcome measures included the Battelle Developmental Inventory (BDI-2), Bayley Scales of Infants Development (BSID-III), and Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The study promoted therapeutic alliance via high clinician continuity. Putative mechanisms of change in the NBO approach‐ beyond fidelity, dose and therapeutic alliance‐ include parental shifts in affect, reflectiveness, openness and responsiveness towards the infant's experience, and dyadic shifts towards reciprocity (McManus et al., 2020). The study findings support shifts in maternal affect and responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study promoted therapeutic alliance via high clinician continuity. Putative mechanisms of change in the NBO approach‐ beyond fidelity, dose and therapeutic alliance‐ include parental shifts in affect, reflectiveness, openness and responsiveness towards the infant's experience, and dyadic shifts towards reciprocity (McManus et al., 2020). The study findings support shifts in maternal affect and responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis found very low‐quality evidence that the NBO supports infant development and parent‐infant relationship quality, and called for NBO stand‐alone effectiveness trials in at‐risk populations (Barlow et al., 2018). Subsequently, an early intervention study for vulnerable newborns reported positive developmental effects, and a pilot study for vulnerable mothers reported on feasibility and acceptability overseas (Greve et al., 2018; McManus et al., 2020). However, no studies in Australia have trialed the NBO as a standalone intervention or in comparison to existing perinatal care for clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…The NBO approach appears to be a powerful tool to consider when designing new sleep-related interventions. Even in the first months of life, when rhythms involving eating, sleeping, and social interactions are characterized by a lack of regularity, parents seem empowered when they discover their infants’ incipient competences [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening parents' feeling that they understand their infant may improve parent-infant interaction (9). Recent studies have found that NBO may be related to improved parent-infant interaction quality (23,39,40). Furthermore, a pilot study indicates that delivering NBO as a preventive intervention may reduce depressive symptomatology (41).…”
Section: The Newborn Behavioural Observations Systemmentioning
confidence: 99%
“…According to Danish law, no approval from the Danish Ethical Committee (H-18021300) was needed as the study involved no biomedical experiments. The study was carried out according to the guidelines of the Declaration of Helsinki (39), ensuring anonymity and con dentiality of data. All participants were informed of the study's aim and procedures, and both oral and written informed consent were obtained from each participant prior to inclusion.…”
Section: Abbreviationsmentioning
confidence: 99%